Human antibodies produced in mice - Bruggemann, Marianne (Henry Stewart Talks, 2007)
Immune development, Human Ig loci, Transgenesis, Human antibody repertoires, Monoclonal human antibodies, Silencing mouse antibody production, B-cell receptor structure, Flow cytometry, Therapeutic Ig
Archived at 2018/12/10